Application of Constant Resistance and Large Deformation Anchor Cable in Soft Rock Highway Tunnel - Xiaoming Sun; Bo Zhang; Li Gan; Zhigang Tao; Chengwei Zhao (Advances in Civil Engineering)
Muzhailing Highway Extra-long Tunnel in Lanzhou, Gansu Province, China, belongs to the soft rock tunnel in the extremely high geostress area. During the construction process, large deformation of the soft rock occurred frequently. Taking the no. 2 inclined shaft of Muzhailing tunnel as the research object, an NPR (negative Poisson’s ratio) constant resistance and large deformation anchor cable support system based on high prestress force, constant resistance, and releasing surrounding rock pressure was proposed. The characteristics of the surrounding rock under the steel arch support and NPR anchor cable support were compared and analyzed by using 3DEC software. A series of field tests were conducted in the no. 2 inclined shaft, and the rock strength, displacement of the surrounding rock, deep displacement of the surrounding rock, internal force of steel arch, and axial force of anchor cable were measured to study the application effect of the NPR anchor cable support system in tunnel engineering. Moreover, the 3DEC numerical simulation results were compared with the field test results. The research results show that the application of NPR constant resistance and large deformation anchor cable support system in tunnel engineering has achieved good results, and it plays a significant role in controlling the large deformation of the tunnel surrounding rock.